PO.5.105 The effect of belimumab on extra-renal outcomes: results from the phase 3, randomised, placebo-controlled, 104-week bliss-ln study in patients with active lupus nephritis. (27th September 2022) - Weinmann-Menke, J; Okada, M; Arriens, C; Jones-Leone, A; Levy, RA; Gilbride, JA; Furie, R; Yang, N
Abstract : Purpose: The effect of belimumab (BEL) on renal outcomes has been previously demonstrated in the BLISS-LN study in patients with active lupus nephritis (LN).1 Here we evaluate the effect of BEL on pre-specified extra-renal outcomes in patients with LN enrolled in the BLISS-LN study. Methods: In this Phase 3, double-blind, placebo (PBO)-controlled study (GSK Study BEL114054; NCT01639339 ), adult patients with systemic lupus erythematosus (SLE) and biopsy-proven LN (class III, IV, and/or V) were randomised (1:1) to monthly intravenous (IV) BEL 10 mg/kg or PBO, plus standard therapy (ST). Randomisation was stratified by race and treatment regimen (high-dose corticosteroids + either cyclophosphamide followed by azathioprine, or mycophenolate mofetil [MMF] followed by MMF). Primary and major secondary efficacy endpoints and safety have been previously published.1 Extra-renal efficacy endpoints included: change from baseline in SLE Disease Activity Index-2000 (SLEDAI-S2K; excluding renal items); proportion of patients with SLEDAI-S2K organ system improvement (excluding renal involvement); proportion of patients with Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI) worsening; and proportion of patients with prednisone-equivalent dose ≤7.5mg/day and ≤5 mg/day at Week 104. Results: Overall, 448 patients were randomised and received study treatment (safety population: n=224/treatment group; modified intention-to-treat [mITT] population: n=223/treatment group). In total, 91 (20.4%) patients withdrew from the study, mainly due to withdrawal of consent (10.1%). The mean (standard deviation [SD]) SLEDAI-S2K score at baseline was 12.3 (5.0) and mean (SD) SDI score was 0.4 (1.0). Most patients (86.1%) had immunologic SLEDAI-S2K involvement at baseline and 39.2% had mucocutaneous involvement (rash, n=119 [26.7%]; alopecia, n=101 [22.6%]; mucosal ulcers, n=29 [6.5%]). At Week 104, there was a significantly greater change from baseline in SLEDAI-S2K (excluding renal items) in the BEL group than in the PBO group (treatment difference vs PBO [95% confidence interval]: –0.4 [–0.8, 0.0]; p=0.0436; Table 1 ). Among patients with organ system involvement at baseline, at Week 104, greater proportions of BEL-treated patients versus PBO-treated patients had improvements from baseline in the immunologic, cardiovascular/respiratory and vascular SLEDAI-S2K domains, while improvements in mucocutaneous, musculoskeletal and hematologic domains favoured PBO ( Table 1 ). At Week 104, numerically more PBO-treated patients (7.8%) than BEL-treated patients (6.5%) experienced SDI worsening while on treatment (p=0.7293; Table 1 ). At Week 104, significantly more BEL-treated patients versus PBO-treated patients were receiving average prednisone-equivalent doses of ≤7.5 and ≤5.0 mg/day (p=0.0139 and p=0.0444, respectively; Table 1 ). Conclusions: The 104-week BLISS-LN study demonstrated that some extra-renal outcomes and steroid dose reduction favoured BEL, compared with ST alone in patients with active LN. Reference: Furie R, et al. N Engl J Med 2020;383 :1117–28. Funding: GSK.